Effect of Preparation Technique on Microstructure and Hydrogen Storage Properties of LaNi3.8Al1.0Mn0.2 Alloys. Issue 12 (December 2016) - Han, X.B.; Qian, Y.; Liu, W.; Chen, D.M.; Yang, K.
Abstract : LaNi3.8 Al1.0 Mn0.2 alloy was prepared by vacuum induction melting and melt-spinning. The effects of different preparation techniques of the as-cast, cast then annealed, as-spun and spun then annealed alloys on the microstructure and hydrogen storage properties were investigated. The results indicated that the non-CaCu5 phases in the alloy became tinier and more dispersive after annealing or melt-spinning compared to those of the as-cast one. But in the spun then annealed alloy, the non-CaCu5 phases disappeared and only a single-phase with CaCu5 type structure was found. For all the alloys, the cell volume was increased in an order of as-cast < spun then annealed < cast then annealed < as-spun, and the change of plateau pressure showed the opposite trend with that of the cell volume. The plateau could be flattened after melt-spinning or annealing, and the spun then annealed alloy showed the minimum plateau slope. The absorption kinetics of the alloy was promoted after melt-spinning or annealing. It is suggested that the change in cell volume and compositional homogeneity resulting from different preparation techniques contribute to the difference of the hydrogen storage properties of the investigated alloys.